2020
DOI: 10.1093/ehjci/ehaa946.3053
|View full text |Cite
|
Sign up to set email alerts
|

Post-load glucose spike is a determinant of post-MI prognosis in patients without known or newly diagnosed diabetes

Abstract: Background Post-prandial plasma glucose spikes contribute to the progression of atherosclerosis. Glycaemic variability may predict post-ACS prognosis. A third to two-thirds of these patients had diabetes mellitus (DM). Post-ACS prognosis is worse in DM than in those without. This has not been tested in patients without DM. Purpose To test whether post-load spike in plasma glucose in patients without known or newly diagnosed D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Most studies reported the incidence of IGT or combination of IFG and IGT. IFG and IGT were combined to comprise the prediabetes group (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Table 1 summarizes characteristics and main results of all studies in our analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies reported the incidence of IGT or combination of IFG and IGT. IFG and IGT were combined to comprise the prediabetes group (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Table 1 summarizes characteristics and main results of all studies in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have demonstrated an increased prevalence of CV risk factors long before the onset of diabetes (35). The relationship between ASCVD risk and 2-h plasma glucose concentration is a continuum, and the increased CV risk begins at a range below the threshold for diabetes diagnosis (24). However, glycemia is not the only factor that influences coronary artery disease risk (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation